SYNTHESIS OF SILVER NANOPARTICLES FROM ANDROGRAPHIS PANICULATA AND EVALUATION OF THEIR ANTIBACTERIAL ACTIVITY - V, SARATHA; S, SUBASRI; S, USHARANI (Innovare Journal of Life Sciences, 2018)
Abstract Aim: Â Andrographis paniculata is one of the most important antibacterial effects. The result proved Andrographis paniculata have antibacterial activity. The objective of this study to synthesis of silver nanoparticles from Â Andrographis paniculata Â and evaluate antibacterial method. Methods: Synthesis of silver nanoparticles from Andrographis paniculata leaves was done by using 1mM AgNO3 solution and incubates 24hr at room temperature. Â Characterization of synthesized nanoparticles was done by Â Â Â Â Â Â Â UVâ€“Vis absorption spectroscopy, FTIR analysis, SEM analysis and Â antibacterial activity. Results: In this result synthesized AgNPs from leaf extract of Andrographis paniculata showed potential antibacterial activity with various human pathogenic bacteria. Antibacterial activity of the silver nanoparticles was performed by a disk diffusion method. The highest antibacterial activity of AgNPs synthesized by Androraphis paniculataÂ leaf Â was found against Salmonella typhi (30 mm). The AgNPs synthesized in this process were found to have efficient antibacterial activity against human pathogenic bacteria. Conclusion: In totality, the AgNPs prepared are safe to be discharged in the environment and possibly utilized in processes of pollution remediation. Â AgNPs may also be efficiently utilized in agricultural research to obtain better health of crop plants as shown by our study. The study concluded that the AgNPs from Andrographis paniculata leaf extract have potential antibacterial activity.